Human capital and human resource management to achieve ambidextrous learning: A structural perspective - Mirta Diaz-Fernandez; Susana Pasamar-Reyes; Ramon Valle-Cabrera (BRQ Business Research Quarterly, 2017)
Organisational learning has become increasingly important for strategic renewal. Ambidextrous organisations are especially successful in the current environment, where firms are required to be efficient and adapt to change. Using a structural approach, this study discusses arguments about the nature of ambidexterity and identifies the kinds of human capital that better support specific learning types and HRM practices suited to these components of human capital. Results highlight learning differences between marketing and production units, as well as different HRM practices and human capital orientations. This study points out that human capital mediates between HRM practices and learning."
Keywords: 650; Ambidextrous learning; Organisational learning; Human capital; HRM practices